(untitled) (Dentika: Dental Journal, 2014)
Matrix system used bis-GMA was reported hazardously. An alternative monomer such as 1,6-hexanediol dimethacrylate (HDDMA) was under research. The aim of this study was to evaluate residual monomer content of HDDMA based matrix compositions on FRCs (fiber-reinforced composites). Three monomers based on bis-GMA (Sigma-Aldrich,USA), methylmethacrylate (MMA, ProSciTech, Australia), HDDMA (Esstech, USA) were used and also camphorquinone (CQ, Esstech, USA), N,N-cyanoethyl methylaniline (CEMA, Esstech, USA), E-glass fibers (StickTech, Finland). The matrix ratios (weight %) were 78.4% bis-GMA+19.6% MMA+1.0% CQ+1.0% CEMA (control-group), 78.4% HDDMA+ 19.6% MMA+1.0% CQ+1.0% CEMA (EXP-1group), and 49.0% HDDMA+49.0% MMA+1.0% CQ+1.0% CEMA (EXP-2group). Samples with fibers embedded in matrix were light-cured then powdered. Powder of 150mg was diluted in acetonitrile to 10ml. The solution was filtered then injected into HPLC (20µL). Residual monomer content was evaluated by mobile phase of acetonitrile and water of 7:3, flow rate 1mL/minute. The size of column was C185µ, 125mm length, 4mm diameter. UV detection used 275nm. Data were analyzed by ANOVA. The result showed the average of residual monomer content (in %) was: 0.02125±0.00018 (control-group), 0.01660±0.00016 (EXP-1group), 0.01676±0.00033 (EXP-2group). The ANOVA showed significant difference of monomer content among the groups (p<0.05). The LSD showed significant difference between EXP-1 and control-groups; also between EXP-2 and controlgroups (p<0.05). There was no significant difference between EXP-1 and EXP-2 groups (p>0.05). In conclusion, a resin matrix system based on HDDMA–MMA (EXP-1 and EXP-2 groups) revealed significant difference of residual monomer content to bis-GMA–MMA (control-group) system. The HDDMA-MMA matrix system had less residual monomer content than bis-GMA-MMA.